Transparency in Human Capital Disclosure in Non-Financial Reporting: Towards Ethical Governance and Corporate Social Responsibility in Banking - Yuliia Serpeninova; Peter Partila; Alina Raboshuk; Olena Krukhmal; Yuliia Nezhyd (Business Ethics and Leadership)

(untitled)
This paper analyzes and compares the non-financial reporting practices on human capital among the three largest banks operating in Slovakia: Slovenská sporiteľňa, Tatra banka, and Všeobecná úverová banka. As sustainability reporting becomes a key component of corporate transparency, ethical governance, and strategic management, human capital disclosure emerges as a crucial dimension of corporate social responsibility. The study aims to evaluate the quality, consistency, and scope of human capital disclosures in the selected banks’ annual and sustainability reports for 2023. A set of 20 key performance indicators (KPIs) was developed and grouped into four categories: basic employee characteristics, diversity and inclusion, employee development and engagement, and employee well-being. Each indicator was evaluated using a scoring methodology based on the level of transparency. Results show that Slovenská sporiteľňa demonstrated the most comprehensive reporting practices, scoring 19 out of 20 points. Tatra banka ranked second with 8.5 points, while VÚB received the lowest score of 6 points, mainly due to the absence of disaggregated data at the local level. The study highlights the variance in disclosure practices and the challenges faced by subsidiaries reporting under consolidated statements. The methodology offers a replicable tool for evaluating human capital disclosure quality and can serve as a benchmark for future analysis after the implementation of the Corporate Sustainability Reporting Directive (CSRD) in the European Union.